“Factores que inciden en la prevalencia de bronquitis aguda en niños de 5 a 10 años en la ciudadela San Miguel Cantón Montalvo Los Ríos primer semestre 2018” - María Fernanda Acurio Jara, María Fernanda (2018)
The present research project focused on the understanding that environmental factors affect the prevalence of acute bronchitis in children aged 5 to 10, for which the general objective was to design an action plan on climate talks in order to stop the acute bronchitis in the citadel San Miguel canton Montalvo, for the development of the investigation, to propose a descriptive, field and bibliographical methodology, which helped us to collect reliable and favorable data for the project, in such a way it was concluded that environmental factors represent a danger to respiratory health, being the most vulnerable children, generating this disease, common diseases in children such as influenza, cold, asthma and more common, acute bronchitis, in addition, parents are trained Children of the San Miguel citadel on how to act in the face of climate changes, as an act against sickness ades, breathing, graves and stopping their evolution.